Re-emphasising the Physical School: Lessons from COVID-19 - Khetan, Neelima; Dewan, Hriday Kant (Voices of Teachers and Teacher Educators, 2021)
COVID-19 brought about several unforeseen situations. One of them was the virtual locking up of children and their inability to go to schools or anywhere else. They missed their peers and their friends, their school and their classrooms, their freedom and their exploration, and for many, their midday meals too. Not surprisingly, given the overwhelming fear of the pandemic, these concerns about what was happening to children lay buried for a long time. Even when the conversation began around school closure, it was largely around the learning gaps that were accruing consequent to the loss of school time. There was pressure on the system to start some teaching process so as to mitigate the time lost and urgency for the school to start doing something to ensure that children were occupied with studies and did not lose out.